PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SEKTOR INDUSTRI PERIODE 2019-2022 - MARSELA ANGGI YANI; Murni, Yetty; Sudarmaji, Eka (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2024)
The aim of this research is to examine the impact of profitability, capital structure and corporate social responsibility on company value, with company size as a moderating variable in the industrial sector listed on the Indonesia Stock Exchange. The research was conducted for four years, starting from 2019 to 2022. A total of 17 companies were selected as research samples that met the criteria using a purposive sampling method. The hypothesis was tested using multiple linear regression analysis using Eviews 12 software. The research results show that profitability, capital structure and company size have a significant impact on company value. Company size is able to moderate the influence of capital structure and corporate social responsibility on company value. However, corporate social responsibility does not have a significant influence on company value, and company size does not moderate the effect of profitability on company value.